The Democratic state - Benjamin, Roger W.; Elkin, Stephen L. (Studies in government and public policy., 1985)
This collection of five original essays by seven of the best-known political-economy theorists addresses the interconnections between the economy and the polity and embodies the leading theoretical approaches to the political economy of the state. -- Amazon.com.